The relationship between steps of 6MWT and COPD severity: a cross-sectional study - Zeng GS (International Journal of COPD, 2018)
Guan-Sheng Zeng,* Li-Chang Chen,* Hui-Zhen Fan, Ling-Ling Wu, Xi-Ping Wu, Ze-Kui Fang, Xi He, Hua-Peng Yu Department of Pulmonary and Critical Care Medicine, Zhujiang Hospital, Southern Medical University, Guangzhou, China *These authors contributed equally to this work Background and objective: The distance of 6-minute walk test (D6MWT) has been widely used in the assessment of functional status in patients with COPD, while very little attention has been paid to the role of steps of 6-minute walk test (S6MWT). The purpose of this study was to investigate the relationship between S6MWT and other physiologic parameters of COPD. Patients and methods: Seventy patients with stable COPD were enrolled consecutively in this cross-sectional study. Pulmonary function tests, including spirometry, impulse oscillometry (IOS) and the single-breath diffusing capacity of the lungs for carbon monoxide (DLCO), were carried out at rest. Quality of life was assessed by health-related quality of life (HRQoL) questionnaires, including modified Medical Research Council dyspnea scale (mMRC), St George’s Respiratory Questionnaire, Chronic Obstructive Pulmonary Disease Assessment Test (CAT) and Clinical Chronic Obstructive Pulmonary Questionnaire. Both steps and distance were measured in the following 6-minute walk test (6MWT). Results: Both S6MWT and D6MWT showed significant correlation with spirometry, IOS, DLCO parameters and HRQoL questionnaires score. Both pre- and post-6MWT inspiratory capacity showed significant correlation with S6MWT (ρ=0.338, P=0.004; ρ=0.359, P=0.002, respectively), whereas did not correlate with D6MWT (ρ=0.145, P=0.230; ρ=0.160, P=0.189, respectively). In stepwise multiple regression analysis, mMRC grade, age and CAT score remained as significant predictors in the final model for D6MWT (adjusted R2=0.445, P<0.01). DLCO and CAT score remained as significant predictors in the final model for S6MWT (adjusted R2=0.417, P<0.01). Conclusion: S6MWT is efficient in the evaluation of functional status and quality of life in COPD and has significant correlation with various parameters indicating disease severity. Additionally, S6MWT might be better in predicting lung hyperinflation in COPD compared with D6MWT. Keywords: COPD, steps, 6MWT, hyperinflation